Parental perspectives on the awareness and delivery of preconception care - M. Poels; M. P. H. Koster; A. Franx; H. F. van Stel (BMC, 2017)
Abstract Background The attention for Preconception Care (PCC) has grown substantially in recent years, yet the implementation of PCC appears challenging as uptake rates remain low. The objective of this study was to assess parental perspectives on how PCC should be provided. Methods Recruitment of participants took place among couples who received antenatal care at a Dutch community midwifery practice. Between June and September 2014, five focus group sessions were held with 29 women and one focus group session with 5 men. Thematic analysis was conducted using NVivo 10 software. Results Participants were generally unfamiliar with the concept of PCC. It was proposed to raise awareness by means of a promotional campaign, stipulating that PCC is suited for every couple with a (future) child wish. Suggestions were made to display marketing materials in both formal and informal (local community) settings. Addressing existing social networks and raising social dialogue was expected to be most efficient. It was recommended to make PCC more accessible by offering multiple forms and to involve male partners. Opportunistic offering PCC by healthcare providers was considered more acceptable when the subject was deliberately raised, for example while discussing contraceptives, lifestyle risks or drug prescriptions. GP's or midwifes were regarded the most suitable PCC providers, however provider characteristics such as experience, empathy and communication skills were considered more important. Conclusions This study showed that from the parental perspective it is recommended to address every couple with a (future) child wish by means of enlarging the awareness and accessibility of PCC. In order to enlarge the awareness, it is recommended to address social networks, to raise the social dialogue and to conduct promotional campaigns regarding PCC. In order to improve the accessibility of PCC, it was suggested to simultaneously offer multiple forms: group sessions, individual consultations, walk-in-hours and online sessions, and to involve male partners.